(untitled) (Research, Society and Development, 2020)
The new contemporary organizational demands, referring to adherence to capital, labor processes with a home-office focus, emergence and adaptations of new professions, etc., have led the worker to constant labor volatility. Not only are decisions required in the market-worker-organization relationship that lead to creativity and productivity, but also to maintain health, especially the mental health of the entire workforce in the social, intellectual, cultural and technological space in work environment. In that sense, studies on Positive Organizational Behavior contribute to the assessment of how and why it is necessary to develop the psychological capacities of workers aimed at quality in the work and social performance of employees. This article intends to verify how much organizational support influences psychological capital and knowledge management and is related to emotional disorder. 208 workers, men and women, from public and private organizations participated in the survey, answering a questionnaire with the scales of organizational support, positive psychological capital, knowledge management, emotional disorder and sociodemographic data. It was observed that all scales were reliable for the evaluation of the theoretical construct, however the intended model was not significant, allowing to generate an alternative model with better explanatory capacity, revealing that the greater the organizational support, the greater the psychological capital, the greater the management of the knowledge and less emotional disorder. These results highlight the importance of training positive social skills applied to human resources in terms of work practice and organizational policy capable of favoring greater emotional adjustment, quality in life and work.